Nutritional Status of Working Children as a Neglected Group in Kermanshah West of Iran - Yahya Pasdar; Mitra Darbandi; Seyyed Mustafa Nachvak (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: Working at an early age can have adverse consequences on health. Working children due to their occupational hazards are at risk of communicable and non-communicable diseases such as malnutrition, anemia and growth retardation. This study aimed to determine the nutritional status and prevalence of anemia in working and non-working children. Methods: This case-control study was carried out as cross-sectional, on 90 working and 90 non-working 8-18 year-old boys in Kermanshah. The data gathering tools were demographic and food frequency questionnaires (FFQ). Anthropometric parameters were measured using standard tools. 5 ml blood for blood biomarkers test was collected from the participants. Results: Average height and weight of working children were respectively 3.7 cm and 5.7 kg less than of the non- working children (P = 0.02). Prevalence of iron deficiency in working children was more than double in the non-working children (28% vs 11.3%, P = 0.01). Hemoglobin concentration was less significantly in working children compare to non-working children (p=0.05). The working children as significantly consumed all of the food groups except the bread and cereals less than the non-working children (P <0.001). Conclusions: Working children are at risk to develop anemia and malnutrition so they need to emergencies nutritional supports.